基于SAE J1939的装载机电液换挡辅助试验系统设计 - 刘钊; 吴强; 谢波; 朱玉田 (Jixie chuandong)
Replying to the requirements of the monitoring and diagnosis for electro-hydraulic control system of the wheel loader hydraulic transmission,CAN bus is used to exchange data between PC and the transmission controller,which accorded to SAE J1939 in the application layer.With the application of the software-LabVIEW,the PC-based program is developed to monitor and diagnose the whole electro-hydraulic shift system.Meanwhile,the program can store and re-display some parameters related to the shift quality.The whole assistant experiment system has a simple hardware structure,the character of high durability and friendly human-interface,and is added to the generality and flexibility.